Tramadol Induced Hypoglycaemia: A Case Report - Zaveri, Dhruv; Patel, Riki; Solanki, Pankti; Rane, Jay; Thakkar, Miral (Journal of Pharmacy Practice and Community Medicine)
Tramadol is most commonly used opioid analgesic. It has a very rare and serious endocrine metabolic side effect as hypoglycaemia. The reason behind hypoglycaemia is still unclear but it may lead due to increased insulin concentration and utilization of glucose by muscles. In this report, a patient is prescribed tramadol for toothache. This report focuses on hypoglycaemia due to tramadol administration. Clinical Pharmacists should be at bedside to alert regarding any Adverse Drug Reaction. Regular monitoring of patients can decrease the mortality rate which is occurring due to ADR.
Keywords: Tramadol; Opioid Analgesic; Suspected Adverse Drug Reaction; Hypoglycaemia; Toothache